Inertia Optimization Control Model of AC/DC Sending-End System Based on Multi-source Energy Storage Coordination - Song XIANG; Peng SU; Jian WU; Xin LIU; Jitao MA (Zhongguo dianli, 2023)
To address the low inertia level of AC/DC sending-end systems with high-proportion new energy access, this paper proposes an optimal control method for the inertia of such systems based on multi-source energy storage coordination. First, considering that large-scale new energy access will affect the energy balance of sending-end systems, the paper establishes a power flow equation for AC/DC sending-end systems with a high proportion of wind power. Second, in response to the insufficient inertia support of weak sending-end systems, it puts forward a multi-source energy storage system with electricity, heat, and gas energy conversion and storage equipment and analyzes the system inertia support characteristics under the coordination of multi-source energy storage. On this basis, considering the frequency stability of sending-end systems, an inertia optimization control model is built for AC/DC sending-end systems based on multi-source energy storage coordination. Finally, an AC/DC sending-end system in an area in northern China is used as a simulation example to verify the effectiveness of the proposed model. The model can provide a theoretical basis for the inertia stability control of AC/DC hybrid systems containing large-scale new energy and realize the safe and stable operation of AC/DC sending-end systems.